Modal Sosial Masyarakat KONI: Kajian Pelaksanaan Pasal 40 Undang-Undang No. 3 Tahun 2005 Sistem Keolahragaan Nasional Jawa Tengah - Rustiadi, Tri (Media Ilmu Keolahragaan Indonesia, 2013)
This study focused on the analysis of socialÂ capital of Indonesian National Sports Committee (KONI)Â which is potential to support the implementation of article40 Law No. 3/2005 about the National Sports SystemÂ through networks and partnerships developed by KONI.Â By using qualitative method, this study took setting ofÂ KONI of Regency/City level in Central Java. To answer Â the research questions, we analyzed the factual action done by KONIâs board by using emic analysis and ethicÂ interpretation procedures. The result was analyzed basedÂ on the board relation with the structural/public figures,Â the developed networks, leadership, and achievementÂ which has been accomplished. The conclusions are: (1)Â The social networks developed by KONI have not beenÂ maximized, for instance, KONI has not involved NGOs toÂ fund the sports development; (2) The social capital of KONIÂ including trust, social network, and authority structureÂ have not been maximized, while the shared norms andÂ shared values have been developed wellÂ